Effect of Single Axis Solar Tracking System on the Performance of Photovoltaic System: A Comparative Experimental Study - Singh , Ravindra Pratap (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays the demand for energy increased rapidly duo to escalating population and global technological development. Consequently, the focus on non-conventional energy sources is increasing rapidly due to change in climates and unhealthy environment caused by fossil fuels. Solar energy is vital to fulfill this growing need of clean energy. The performance of the photovoltaic (PV) technology used for capturing sun’s radiation is directly affected by solar irradiation. The optimum performance of the PV systems would be possible if the solar panel is always orientated towards the direction of maximum radiations of sun. Hence, in order improve the performance of the PV, tracking of maximum radiation of the sun is extremely important. In this experimental study, solar tracking is done using a single axis solar sun tracker which not only provides accurate but also cost efficient solar sun tracking in comparison with an existing stationary system of same capacity. The results show that a single axis solar tracking systems have generated approximately 28.3% more compared to static systems and is also found to be more economic than a solar tracking system which uses microcontroller.